An approach towards co-operative auditing and its problems: a case study on Jabatan Pembangunan Koperasi Wilayah Persekutuan / Hashim Anuar - Anuar, Hashim (1987)
This research paper is prepared in order to explain and highlight the process of auditing to the various co-operatives carried out by Jabatan Pembangunan Koperasi and also to find out and determine the problems of auditing faced by them.